Cephalosporin C acylase: Important role, obstacles, and strategies to optimize expression in E. coli - Muthi’ah Rasyidah, Sismindari Sismindari, Purwanto Purwanto (Journal of Applied Pharmaceutical Science, 2024)
Cephalosporins have gained popularity due to the increasing resistance to penicillin antibiotics. Since the first discovery of cephalosporin C in 1945, the development of cephalosporin-class antibiotics has continued. Cephalosporin C was converted into a 7-aminocephalosporanic acid (7-ACA) compound which became a precursor for producing cephalosporin class antibiotics through side chain modification. The conversion of cephalosporin C to 7-ACA is more beneficial when performed enzymatically using the enzyme cephalosporin C acylase (CA) compared to chemical methods. This article will present the importance of cephalosporin CA enzymes in the development of cephalosporin antibiotics, the obstacles, and strategies to optimize the expression of these enzymes in Escherichia coli hosts.
Keywords: Cephalosporin, 7-ACA, cephalosporin C acylase, E. coli